2016
DOI: 10.3892/etm.2016.3323
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory molecules expression pattern for identifying pathogen species in febrile patient serum

Abstract: Abstract.Inflammatory molecules, such as cytokines and chemokines, have been considered markers for bacterial or viral infection in serum of patients in numerous studies. The aim of the present study was to investigate whether we were able to identify the pathogen species through patterns of inflammatory molecules. A total of 132 patients with elevated body temperature (tympanic temperature, >38.3˚C) were recruited for this study. The concentrations of various inflammatory molecules in the patients' serum were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
(55 reference statements)
0
2
0
1
Order By: Relevance
“…In regards to cytokine signature during SARS-CoV-2, studies showed an adapted, controlled response in mild and moderate cases with higher expression of IL-1β, IL-1RA, IL-2RA, IL-6, IL-7, IL-8, IL-9, IL-10, basic FGF, G-CSF, GM-CSF, HGF (hepatocyte growth factor), IFNγ, IP-10, MCP-1, MIP-1a, MIP-1b, PDGF, TNF-α and VEGF compared to a healthy control as shown in Figure 4 [ 2 , 126 , 219 ]. These results are summarized and compared to other infectious settings in Table 2 [ 126 , 220 , 221 , 222 , 223 , 224 ].…”
Section: Immunopathology Of Sars-cov-2mentioning
confidence: 99%
“…In regards to cytokine signature during SARS-CoV-2, studies showed an adapted, controlled response in mild and moderate cases with higher expression of IL-1β, IL-1RA, IL-2RA, IL-6, IL-7, IL-8, IL-9, IL-10, basic FGF, G-CSF, GM-CSF, HGF (hepatocyte growth factor), IFNγ, IP-10, MCP-1, MIP-1a, MIP-1b, PDGF, TNF-α and VEGF compared to a healthy control as shown in Figure 4 [ 2 , 126 , 219 ]. These results are summarized and compared to other infectious settings in Table 2 [ 126 , 220 , 221 , 222 , 223 , 224 ].…”
Section: Immunopathology Of Sars-cov-2mentioning
confidence: 99%
“…Por otra parte, la respuesta inmune del hospedero frente a diversos patógenos ha sido estudiada mediante la medición de citoquinas, moléculas efectoras esenciales para la respuesta inmune innata y adaptativa 12,13 . Si bien, en el paciente inmunocompetente se han caracterizado perfiles para diversos patógenos 14,15 , hay poca evidencia sobre la respuesta local y producción de citoquinas en receptores de TPH ante una IRV.…”
Section: Investigación Clínicaunclassified
“…( 10 ) It is speculated that BCAA metabolism in brown adipocytes changes during infection and affects [BCAA], especially in patients with bacterial pneumonia. As amino acids are essential nutrients for the host and the pathogen in infectious diseases, ( 11 ) the metabolic crosstalk between the host and the pathogen regarding amino acids is attracting attention. ( 12 , 13 ) Regarding BCAA interrelationships, Ile and Val suppress Leu metabolism in human peripheral lymphocytes, ( 14 ) and each BCAA has a different effect on immune function.…”
Section: Introductionmentioning
confidence: 99%